Living Donor Kidney Transplantation in Patients With Donor-Specific HLA Antibodies After Desensitization With Immunoadsorption - Kälble, Florian; Süsal, Caner; Pego da Silva, Luiza; Speer, Claudius; Benning, Louise; Nusshag, Christian; Pham, Lien; Tran, Hien; Schaier, Matthias; Sommerer, Claudia; Beimler, Jörg; Mehrabi, Arianeb; et al. (Frontiers in Medicine, 2021)
Due to the organ shortage, living donor kidney transplantation is increasingly performed across HLA (human leukocyte antigen) or ABO antibody barriers. There is still uncertainty about the risk of antibody-mediated rejection (AMR) episodes, which may limit long-term graft survival. Thirty-eight desensitized living donor kidney transplant recipients were included in the study. Nineteen patients had a positive CDC crossmatch result with their donor and 36 patients had Luminex-detected donor-specific HLA antibodies (DSA). The patients were successfully desensitized with a median of 8 immunoadsorption treatments; 12 patients received additional plasma exchange. After desensitization but before transplantation, the patients received the anti-CD20 antibody rituximab (N=36) in combination with thymoglobulin (N=20) or anti-IL2 receptor antibody (N=18). The results of the 38 desensitized patients were retrospectively compared to the results of 76 1:2-matched standard-risk recipients. Desensitized patients showed patient and graft survival rates similar to that of standard-risk recipients (P=0.55 and P=0.16 respectively). There was a trend towards reduced death-censored graft survival in desensitized patients (P=0.053) which, however, disappeared when the 34 patients who were transplanted after introduction of sensitive Luminex testing were analyzed (P=0.43). The incidence of rejection episodes without borderline changes were with 21% in desensitized patients similar to 18% in standard-risk patients (P=0.74). Thirty-six patients had pre-transplant HLA class I and/or II DSA that were reduced by 85% and 81%, respectively, during pretransplant desensitization (P<0.001 for both). On day 360 after transplantation, 18 of 36 (50%) patients had lost their DSA. The overall AMR rate was 6% in these patients, but as high as 60% in 5 (14%) patients with persistent and de novo DSA during year 1; 2 (40%) of whom lost their graft due to AMR. Eleven (31%) patients with persistent DSA but without de novo DSA had an AMR rate of 18% without graft loss. Our desensitization protocol for pre-sensitized living donor kidney transplant recipients with DSA resulted in good graft outcomes with side effects and rejection rates similar to that of standard-risk recipients. Adequate patient selection prior to transplantation and frequent immunological monitoring thereafter is critical to minimize rejection episodes and subsequent graft loss.